Pendampingan Usaha Kecil dan Menengah Mekarsari Dalam Peningkatan Kualitas Usaha - Adrian, Adrian; Mahendra, Arista; Pranoto, Claresta; Putri, Farahayu Galuh; Gavrila, Natasha; Nathan, Wilbert; Wijanarko, Winston; Ervina*, Dahlia (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
The rapid development of Micro, Small and Medium Enterprises in Indonesia is one of the reasons the Community Service (PKM) activities are being held by Prasetiya Mulya University. Aside from being a learning facility for students, this activity also aims to help residents of Cianjur, especially in the village of Cipendawa, to improve the quality and develop their business. In this journal, the programs main focus is to help Mekarsari, a business that sells snacks and snacks since 1996. To improve product quality, efficiency, and productivity, the writing team replaced damaged production equipment, changed the layout of the workstation for packaging and storage, installing stickers on product packaging, consignment at food stalls, and providing debriefing for daily freelancers and bookkeeping. The achievements of this activity are a decrease in the number of defects and increased productivity in the production process, increasing efficiency in the packaging process, adding distribution channels, giving identity to products by giving stickers, and business’ owner being able to take notes of cash flow neatly and systematically.